Dampak Keberadaan Tempat Pembuangan Akhir (TPA) Sampah Terhadap Peningkatan Pendapatan Masyarakat Pemanfaat TPA Muara Fajar Kota Pekanbaru - Wulandari, Tiara; Ekwarso, Hendro; Asrina, Putri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study aims to analyze the impact of the existence of the Muara Fajar Waste Disposal Site (TPA) in Pekanbaru on the income of the surrounding community. The research method employed is a qualitative approach, with data collection through in-depth interviews with community members involved in activities at the TPA, including scavengers, waste managers, and other economically impacted residents. The results show that the presence of Muara Fajar TPA has a positive impact on the increase in income for the surrounding community, particularly through waste management activities such as sorting, collecting recyclable items, and processing organic waste. Most informants reported an increase in income after being involved in TPA activities, although difficulties remain in meeting basic needs such as school fees, especially for higher education. This study concludes that while the TPA contributes to the economic well-being of the community, significant challenges remain in managing family finances and meeting educational needs. Therefore, it is recommended to develop sustainable community empowerment programs and provide educational support for low-income families to improve their overall well-being.